2000
DOI: 10.1097/00007435-200003000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Patient-Administered Tampon Specimens for Chlamydia trachomatis and Neisseria gonorrhoeae

Abstract: Both commercial assays can be applied to tampon-collected specimens for automated detection of sexually transmitted diseases. The detection of C trachomatis was similar to the in-house PCR test for both assays (P = 0.73, 0.68). Detection of N gonorrhoeae resulted in fewer positive tampon specimens when tested by ligase chain reaction than both Roche Amplicor and in-house PCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…The three COBAS Amplicor-positive and omp1 PCR-negative anal samples all contained adequate amplifiable DNA and a lack of inhibitors, as shown by ␤-globin detection (14,21,22). It is most probable that these samples were not false positives, but rather contained bacterial levels that were below the detection level of the omp1 PCR assay.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The three COBAS Amplicor-positive and omp1 PCR-negative anal samples all contained adequate amplifiable DNA and a lack of inhibitors, as shown by ␤-globin detection (14,21,22). It is most probable that these samples were not false positives, but rather contained bacterial levels that were below the detection level of the omp1 PCR assay.…”
Section: Discussionmentioning
confidence: 95%
“…DNA was isolated directly from the clinical samples by using the automated MagNA Pure LC (Roche Diagnostics), and the COBAS Amplicor PCR assay was performed as previously described (21). An additional PCR for amplification of ␤-globin sequence was conducted for detection of inhibition and sample adequacy (22).…”
Section: Methodsmentioning
confidence: 99%
“…por VR typing is not designed to be a diagnostic test per se but rather a method that can be used in conjunction with NAAT to characterize strains in individuals who have been identified as having gonococcal infections. Several studies have shown that endocervical and vaginal samples are more sensitive than urine for detecting gonococci in women (6,15,17,23,26), and the use of self-collected vaginal swabs might be a viable alternative (17,26). In studies where urine samples are collected, centrifuging the samples and storing the pellets alone may improve subsequent genotypic analyses.…”
Section: Vol 43 2005mentioning
confidence: 99%
“…NAAT are more sensitive than culture (32) and are used to test noncultured samples such as urine, vaginal swabs, and tampons (15,23,26). Therefore, NAAT can be used to easily screen individuals, including those who are asymptomatic, without the need for a physical exam.…”
mentioning
confidence: 99%
“…More recently, detection of chlamydial infection by these techniques has also been assessed on secretions recovered from vaginal introitus collected by clinicians or patients themselves (2,5,9,15,16,22,26,31,33) or from vaginal tampons (13,(23)(24)(25). Urine and self-collected samples represent easy and noninvasive techniques compared to the usual cervical swabbing, which necessitates vaginal speculum insertion and a gynecologic examination.…”
mentioning
confidence: 99%